The vascular protective effects of polyphenols. - Md. Jaffri, Juliana (IIUM Press, 2011)
Polyphenols have been proven, both in animal and human studies to be beneficial as vascular protective agents. The effect is claimed to be related to the compound antioxidative properties. This effectively blunts the vasoconstriction process, reported to be due to the excessive generation of reactive oxygen species, as observed in many in vitro studies using isolated arteries. The mechanism ofthe vasodilation process invo Ived the endothelium, or it could also be endothelium-independent. In many studies the fornler seemed to be the main pathway. The role of nitric oxide in endothelium-dependent vasodilation activity of the polyphenols is attributed to its protective effect on the soluble gas from deterioration by ROS, as it is capable of neutralizing the radicals. Polyphenols has also been proven to stimulate endothelial nitric oxide synthase to produce more NO, and hence improve vasorelaxation